Features of non-coaxial strain and modelling of accumulated strain under principal stress rotation induced by train loads in soft clay. Issue 9 (28th July 2020) - Shen, Yang; Wang, Jun-Jian; Xu, Hai-dong; Liu, Han-Long; Wang, Qin-Cheng
Abstract: Foundation settlement under long-term train loads is a realistic engineering issue. Train loads can cause a different stress path and non-coaxial strain compared to other loads. The non-coaxial strain cannot be ignored when evaluating permanent settlements of rail foundations. The keynote of this paper is to investigate the dynamic behaviour of soft clay under cyclic train loads. A number of hollow cylinder tests on reconstituted soft clay specimens were carried out under the heart-shaped stress paths and compared with the round stress paths. It is found that the influence of cycle times on non-coaxial angle under the heart-shaped stress path is not obvious. The curves between non-coaxial angle and the major principal stress directional angle fluctuate with the frequency increasing. According to curves of deviatoric strain increment vs. major principal stress directional angle, the fluctuation can be seen as a negligible impact. A liner relation between non-coaxial angle and the major principal stress directional angle without considering the frequency is established. The generalised plastic potential theory model considering the principal stress rotation, but the non-coaxiality was ignored. Therefore, a modified model considering non-coaxiality is proposed. Comparison between computed results and experimental data has been done to verify the proposed model. Results show that the proposed model can reasonably predict strain in most cases under consideration.